Continuous vs. cyclic combined hormonal contraceptives for treatment of dysmenorrhea: a systematic review - Tiffany Damm; Georgine Lamvu; Jorge Carrillo; Chensi Ouyang; Jessica Feranec (Elsevier, 2019)
Objective: This systematic review aims to evaluate the benefits of oral continuous combined hormonal contraceptives (CHCs) in managing dysmenorrhea by comparing randomized controlled trials (RCTs) evaluating the efficacy of continuous vs. cyclic CHC use for the following outcomes: (a) reducing dysmenorrhea duration and frequency, (b) severity, (c) recurrence and (d) interference with daily activity. Study design: Cochrane, PUBMED and Popline databases were searched from 1934 to 2018 for all relevant studies evaluating CHC for treatment of dysmenorrhea. A study was selected if it (a) compared continuous regimen vs. cyclic regimen of oral CHC, (b) measured dysmenorrhea as a primary or secondary outcome, (c) was an RCT and (d) was published in English. Due to differences in CHC used and outcome measurement, a systematic analysis of individual study results and a limited meta-analysis were conducted. Results: Of 780 studies that were screened by title and abstract, 8 were included in the final analysis; 6 evaluated cyclic vs. continuous CHC, and 2 evaluated cyclic vs. extended/flexible CHC use. Quality of evidence was low for all outcome measures. Overall, compared to cyclic use, flexible/extended CHC resulted in 4 fewer days of dysmenorrhea. Studies revealed conflicting results for interference with daily activity, pain severity and pain recurrence. Side effects were few in both comparison groups. Conclusions: Continuous or extended/flexible CHC use may reduce dysmenorrhea duration compared to cyclic regimen; however, more rigorous research is needed. Implications: This systematic review shows that continuous CHC use may reduce dysmenorrhea duration compared to cyclic regimen, although the quality of evidence is low. Future double-blinded RCTs with more rigorous study design, consistent outcome measures and comprehensive outcome reporting are needed. Keywords: Dysmenorrhea, Oral contraceptives, Hormonal contraceptives, Treatment